Psittacanthus corderoi, a new species of Loranthaceae from the colombia Amazonia (2016)
Psittacanthus corderoi F. González, F. J. Roldán and Pabón-Mora, a species from the department of Amazonas, Colombia, is here described and illustrated for the first time. The new species is similar to P. lasianthus Sandwith, from Guyana and Venezuela, but it differs by various vegetative and floral traits. The most conspicuous diagnostic trait is the presence of numerous laciniae to 2 mm long on the outer surface of the petals, a trait unique in the genus.